Novel Laccaria Species From Juglandaceae Forest in Panama With Notes on Their Ecology - Corrales, Adriana; Wilson, Andrew W.; Mueller, Gregory M.; Ovrebo, Clark (Frontiers in Microbiology, 2020)
Since 2013 there have been 20 new species of Laccaria described worldwide. Only three of these represent species from the neotropics. In Panama, Laccaria is abundant in monodominant Oreomunnea mexicana (Juglandaceae) forests based on sporocarps and environmental sequencing of roots. This study uses a combination of morphological and phylogenetic evidence to document up to seven species of Laccaria from these forests, one previously described, three described as new, and three requiring more data before being formally described. Molecular data used for phylogenetic analysis include the nuclear ribosomal ITS and 28S regions, along with TEF1 and RPB2. Laccaria stellata, has previously been reported from O. mexicana cloud forests of Panama. L. dallingii sp. nov., Laccaria nitrophila sp. nov., and L. fortunae sp. nov. are described as new based on morphology and phylogenetic analysis of multiple collections. A taxon referred to as “PAN sp3” is resolved sister to L. stellata. Phylogenetic analysis also resolved two separate clades of Panamanian Laccaria as sister to L. roseoalbescens, a species previously described from Mexico. These three taxa are not described in this paper as there is too little material from which to make effective morphological descriptions even though their placement in phylogenetic analysis identify them as being unique. Ecologically, all described species except for L. fortunae were amplified from O. mexicana ectomycorrhizal root tips. L. nitrophila was one of the most recovered species from the roots of O. mexicana in a previous study, and it has been shown to respond positively to long term nitrogen addition. Our result expands knowledge of Laccaria diversity for Central America and highlight that at least some species of Laccaria are nitrophilic in neotropical Juglandaceae forests as well as in temperate forests.